pTDP-43 levels correlate with cell type–specific molecular alterations in the prefrontal cortex of C9orf72 ALS/FTD patients - Hsiao-Lin V. Wang; Jian-Feng Xiang; Chenyang Yuan; Austin M. Veire; Tania F. Gendron; Melissa E. Murray; Malú G. Tansey; Jian Hu; Marla Gearing; Jonathan D. Glass; Peng Jin; Victor G. Corces; et al. (Proceedings of the National Academy of Sciences, 2025)
Repeat expansions in the C9orf72 gene are the most common genetic cause of amyotrophic lateral sclerosis and familial frontotemporal dementia (ALS/FTD). To identify molecular defects that take place in the dorsolateral frontal cortex of patients with C9orf72 ALS/FTD, we compared healthy controls with C9orf72 ALS/FTD donor samples staged based on the levels of cortical phosphorylated TAR DNA binding protein (pTDP-43), a neuropathological hallmark of disease progression. We identified distinct molecular changes in different cell types that take place during FTD development. Loss of neurosurveillance microglia and activation of the complement cascade take place early, when pTDP-43 aggregates are absent or very low, and become more pronounced in late stages, suggesting an initial involvement of microglia in disease progression. Reduction of layer 2-3 cortical projection neurons with high expression of CUX2/LAMP5 also occurs early, and the reduction becomes more pronounced as pTDP-43 accumulates. Several unique features were observed only in samples with high levels of pTDP-43, including global alteration of chromatin accessibility in oligodendrocytes, microglia, and astrocytes; higher ratios of premature oligodendrocytes; increased levels of the noncoding RNA NEAT1 in astrocytes and neurons, and higher amount of phosphorylated ribosomal protein S6. Our findings reveal progressive functional changes in major cell types found in the prefrontal cortex of C9orf72 ALS/FTD patients that shed light on the mechanisms underlying the pathology of this disease.